PERUBAHAN HUKUM ADAT PADA TRADISI PERKAWINAN MASYARAKAT SUKU TORAJA DI LEMBANG DENDE’ KABUPATEN TORAJA UTARA - Noling, Lois Banne; Purwanto, A.; Lumintang, Juliana (Universitas Sam Ratulangi, 2019)
Indonesian ethnic groups depart from members of the community that marriage is a sacred bond and is one of the gifts of the Almighty God that cannot be avoided by mankind. Marriage is not merely a bond between two different men and women but also the process of unification of two families.Marriage is a staple of the culture and the marriage ceremony also has a shift or change. As happened to the life of Toraja people who experience acculturation. In the marriage ceremony of the Toraja tribe community in Lembang Dende ' remained through the stage based on the customary order ranging from the process of the Ma'parampo decay to the stage of the marriage of Rampanan Kapa '.Traditional ceremony of Toraja people's marriage in Lembang Dende ' more clearly know that traditional ceremonies are not merely implemented but must refer to the customs prevailing in Toraja. Marriage procession, especially the customary law contained in it is already a thing that is no longer realized by society so that violations are already a common thing in society. The things that are very fundamental for the Toraja community, especially in Lembang Dende' itself must be preserved so that this culture is not eroded by the time. There are still a lot of elements from the Aluk that will always be refined by all elements of society and hopefully this culture continues to be preserved.Keywords: marriage, ceremony, tribe